SYSTEM OF PSYCHOLOGICAL PREVENTION AND ASSISTANCE TO THE SUBJECTS WITH THE EMOTIONAL BURNOUT SYNDROME - Надежда Ивановна Влах; Игорь Петрович Данилов (Медицина в Кузбассе, 2017)
Subject. Consistent patterns of the genesis and phenomenology of pre-neurotic subdepressive states in emotional burnout.